2019
DOI: 10.1111/cas.14110
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia decreases macrophage glycolysis and M1 percentage by targeting microRNA‐30c and mTOR in human gastric cancer

Abstract: Macrophages are essential inflammatory cells which regulate the features of immune reactions within tumors. Many studies have reported their regulatory roles in immunity through cytokines and cell signaling. However, relatively few studies have focused on their metabolic features and mechanisms. We aimed to determine the signaling pathway regulating cell metabolism and the mechanism related to the regulation of human tumor‐associated macrophages (TAMs) in gastric cancer (GC). Tumor‐infiltrated macrophages were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 34 publications
1
35
1
Order By: Relevance
“…M1-type macrophages can kill tumor cells in multiple ways, while M2-type macrophages promote the occurrence, invasion, and metastasis of the tumors. Zhihua et al [34] reported that the expression of microRNA (miRNA)-30c was significantly reduced in GC. Further studies showed that hypoxia-inducible factor-1α (HIF-1α) inhibited miRNA-30c expression.…”
Section: Macrophagesmentioning
confidence: 99%
“…M1-type macrophages can kill tumor cells in multiple ways, while M2-type macrophages promote the occurrence, invasion, and metastasis of the tumors. Zhihua et al [34] reported that the expression of microRNA (miRNA)-30c was significantly reduced in GC. Further studies showed that hypoxia-inducible factor-1α (HIF-1α) inhibited miRNA-30c expression.…”
Section: Macrophagesmentioning
confidence: 99%
“…To alleviate hypoxia, hyaluronic acid NPs targeted towards TAMs have been designed to increase O 2 production in the TME, showing inhibition of tumor growth and metastasis in 4T1 tumors [ 183 , 184 ]. Inactivation of HIF-1α by restoring miR-30c expression in macrophages showed antitumoral efficacy in gastric cancer [ 185 ]. In other reports, tumor oxygenation was improved by normalizing the tumor vasculature, through inhibition of VEGF or REDD1 in TAMs [ 186 ].…”
Section: Metabolic Manipulation To Reprogram Tamsmentioning
confidence: 99%
“…Animal and experimental studies have supported that TAM can provide a favorable microenvironment to promote tumor progression and metastasis 5,9 . In response to various microenvironment signals, macrophages can shift: M1‐like and M2‐like macrophages have distinct functional phenotypes, and while M1‐like macrophage is involved in the pro–inflammatory response, the M2‐like macrophage promotes the anti–inflammatory response 10‐12 . It is generally accepted that TAM display the M2‐polarized phenotype and are a critical player in the tumor microenvironment 5,13,14 …”
Section: Introductionmentioning
confidence: 99%